Long-Term Performance of Green Company IPOs and Underpricing Factors for Gold Indonesia 2045 - Pratiwi, Dian Eka; Nugroho, Irawan Cahyo; Susanto, Andrianto Sulistiono; Muharam, Harjum (LifeSciFi, 2024)
This study investigates the long-term performance of Initial Public Offerings (IPOs) by green companies and the factors contributing to underpricing within the context of Gold Indonesia 2045. Utilizing a descriptive qualitative approach, the research scrutinizes data sourced from financial reports, IPO prospectuses, and stock prices. It identifies key factors such as company characteristics (size, age, ownership structure, industry sector), market conditions (liquidity, stability, macroeconomic factors), and offering specifics (size, price) to elucidate their impact on stock underpricing during IPOs. Additionally, the study assesses the enduring stock performance of green companies post-IPO, leveraging financial performance metrics including Return on Assets (ROA), Return on Equity (ROE), and revenue growth. The findings aim to provide valuable insights for investors, companies, and policymakers, fostering sustainable business practices in alignment with Gold Indonesia 2045.